Tingkat Kepuasan Pasien Terhadap Pelayanan di Puskesmas Lembang Kabupaten Majene - Muhammad Edward Huznan Rafid (YICI Publisher, 2024)
The quality of service from a health center is one of the factors that will make patients come back for treatment or even leave for life. In the current era, health centers are required to improve the quality of service and the comfort of patients who come for treatment, the problem that occurred at the Lembang health center was a decrease in the number of patient visits in the February - March period of 2023. This study aims to determine the level of patient satisfaction with services at the Lembang health center for the period February - March 2023. This study is a quantitative descriptive study with a cross sectional approach. Data was collected through the distribution of questionnaires given to 385 respondents. Respondents were selected based on predetermined inclusion and exclusion criteria.Respondent characteristics were grouped according to gender, age, latest education level, occupation, payment method, and service area at the puskesmas. Based on gender, respondents were dominated by women (66%), while men amounted to 34%. In terms of age, the majority (43%) were in the 17-35 years range, followed by the 36-55 years age group (33%), and the rest (24%) were over 55 years old. In terms of education, most respondents were high school graduates (43%), followed by junior high school (29%), elementary school (16%), no school/not graduated from elementary school (5%), diploma/graduate degree (7%), and no postgraduate degree. In terms of occupation, 53% are housewives, followed by other groups such as civil servants (6%), traders / self-employed (8%), students (10%), retirees (5%), private employees / employees (10%), laborers (4%), and 4% who do not work.The results concluded that the service element with the lowest Community Satisfaction Index value was the service completion time (3.05), followed by handling complaints/suggestions (3.26) and infrastructure (3.26). This indicates the need to accelerate waiting times, increase the socialization of survey boxes, and develop puskesmas facilities and infrastructure. Based on the evaluation results of 9 elements of the Community Satisfaction Index in accordance with the Regulation of the Minister of Administrative Reform Number 14 of 2017, the IKM value is 3.34. Thus, the level of patient satisfaction with services at the Lembang Health Center is categorized as Good.